Treatment of eutrophoted waters of the interior bay of Puno, Peru, with the use of two macrophytes - Jimenez Monroy, Luis Llberto (2016)
The objective of the investigation was to determine the levels of Total Nitrogen (NT) and Total Phosphorus (PT) of the contaminated waters of the inland bay of the city of Puno, of the sector called Espinar Island, And evaluate the efﬁciency of two macrophytes, such as Elodea Canadensis Michax (llacho) and Myriophyllum quitensis Kunth (fennel) for the removal of nitrogen and phosphorus. To evaluate the samples, from the Parinas sector of the Chucuito Peninsula, the Mega Laboratory of the National University of the High Plateau of Puno (UNA-Puno) was worked. The contaminated waters of the sectors were considered for the study, with mixture (standard water + water of the sector) and without dilution, from 00 to 30 days and from 30 to 60 days. Total Nitrogen was determined using the Kjeldahl method and for the quantiﬁcation of Total Phosphorus the ascorbic acid method was used. The experimental design was of factorial type. The results showed that the average content of Total Nitrogen was 2.21 mg NT / L; While Total Phosphorus was 1.36 mg PT / L. These values are high with respect to the acceptable level of the waters of the bay, which allows to maintain that the inner bay of the city of Puno is eutroﬁzado. On the other hand, Myriophyllum quitensis, analyzed in aquaria, in dilute waters, is more efﬁcient in absorbing the Total Nitrogen (NT) up to 35 days; While Elodea canadensis is more effective at removing Total Phosphorus (PT) ions at 29 days and, undiluted, up to 37 days. This method is an alternative to remedy the waters of the inner bay of the city of Puno, Peru.